Relationship between banks’ credit activity and economic growth: An empirical research for the Republic of Serbia - Grbić, Milka; Luković, Stevan (Industrija, 2020)
The subject of the research in this paper is the interactive relationship between banks’ credit activity and economic growth. Consequently, the aim of the paper is to examine the existence and direction of causal relation between credit activity of banking sector and the overall economic activity in the Republic of Serbia. For the purposes of the survey are gathered quarterly data related to the period 2003–2019. As indicators of credit activity in the study are used the share of loans granted to enterprises in GDP and the share of loans granted to households in GDP, while the rate of growth of real GDP is determined as an indicator of economic growth. Since the observed time series are of different order of integration, the analysis is conducted within the VAR model, with the application of Toda-Yamamoto procedure of the Granger causality test. The results of research show that there is significant unidirectional causal relationship according to Granger which comes from the direction of bank’s credit activity towards economic growth. The results of the analysis can be particularly useful to economic policy measures creators, as well as to creators of development strategies.